The dependence of prices on labour-values - Diego Guerrero (Atlantic Review of Economics, 2011)
It is frequently believed, in a quite schizophrenic fashion, that a theory of value must just solve the question of relative prices (a microeconomic problem), being mainly the theory of money the piece needed for determining the absolute or monetary level of prices (a macroeconomic problem). But on the one hand, the determination of the level of prices is theoretically prior to any consideration of the money market, whereas on the other hand no theory of value can aspire to be complete without the determination of the absolute level of values. It will be shown in this paper that only the Labour theory of value (LTV) can perform both tasks, thus giving completeness and unity to economic theory. It is frequently acknowledged that, as labour is - or is treated as, as the critics of the LTV say - the only factor of production of value (even if it is just one of the several factors producing wealth), the determination of prices is independent of demand in the long run. However, prices are not determined by technical or physical data plus wages, contrarily to what is commonly thought. It is only the couple formed by relative prices and the rate of profit that is determined by them, as well as the couple relative values and the rate of surplus value. By contrast, it can be shown that absolute prices crucially depend on, and in fact are determined by, absolute values, what will be illustrated in this paper by means of a numerical example of an economy with only two industries, where for example halving the quantity of labour or value reduces the level of prices by a 50%. The path of thought that will lead us to these conclusions requires previous clarifications of the several and frequently poorly understood Marxian concepts of value (and price), and a new view on the question of the transformation of value prices (Marx's term) into production prices, both of which will be developed simultaneously with the main line of argument.
Keywords: B51; D46; 330; prices; labour-values; labour theory of value; teoría del valor-trabajo; Arbeitswertlehre; Theorie